Bank Soundness and Sustainability-Evidence From Middle East, Indian Sub-Continent and African Banks - Abdul Hadi, Abdul Razak; Suryanto, Tulus; Tat Hiung, Eddy Yap (IKONOMIKA, 2018)
ABSTRACTThe study is carried out with the objective of examining the effects of bank’s liquidity (LR), non-performing loans (NPL), capital adequacy ratio (CAR), loan growth (FEXP) and default risk premium (FQL) on bank’s performance as measured by return on assets (ROA) within the framework of Basel Committee on Banking Supervision.The financial intermediation theory of banking is reexamined to see how the current banking supervision safeguards the interest of depositors.  Engaging pooled OLS as an estimation tool on 93 commercial banks in Middle East, Africa and Indian subcontinent over study period from 2009 through 2016, the findings reveal thatthere are significant relationships between bank’s performance and its liquidity plus loan growth.  Both ROA and FEXP are also found to be positively correlated.  Even though NPL and CAR do not have significant relationship with ROA, both are found to be negatively correlated with ROA.  Overall, the study has proven that liquidity and loan growth have pivotal roles in sustaining bank’s profitability over time.   Keywords: Bank’s Liquidity, Return on Assets,Capital Adequacy Ratio, Non-Performing Loans, Loan Growth, Static Panel Data, PooledOLS and Basel Committee on Banking Supervision.